2014
DOI: 10.1371/journal.pone.0092136
|View full text |Cite
|
Sign up to set email alerts
|

Viral Replication and Lung Lesions in BALB/c Mice Experimentally Inoculated with Avian Metapneumovirus Subgroup C Isolated from Chickens

Abstract: Avian metapneumovirus (aMPV) emerged as an important respiratory pathogen causing acute respiratory tract infection in avian species. Here we used a chicken aMPV subgroup C (aMPV/C) isolate to inoculate experimentally BALB/c mice and found that the aMPV/C can efficiently replicate and persist in the lungs of mice for at least 21 days with a peak viral load at day 6 postinoculation. Lung pathological changes were characterized by increased inflammatory cells. Immunochemical assay showed the presence of viral an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Cultured Vero cells are the best available substrate for aMPV and have been used to study fuctions of aMPV proteins, entry to cells, mediation to membrane fusion, replication, induction of autophagy and vaccine preparation in previous reports [42][43][44][45][46][47]. aMPV/C is more closely related to hMPV and may have larger cellular host ranges potentially including mammalian than other subtypes [12,48]. In this study, iTRAQ was used for the first time to analyze Vero cells infected with aMPV/C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultured Vero cells are the best available substrate for aMPV and have been used to study fuctions of aMPV proteins, entry to cells, mediation to membrane fusion, replication, induction of autophagy and vaccine preparation in previous reports [42][43][44][45][46][47]. aMPV/C is more closely related to hMPV and may have larger cellular host ranges potentially including mammalian than other subtypes [12,48]. In this study, iTRAQ was used for the first time to analyze Vero cells infected with aMPV/C.…”
Section: Discussionmentioning
confidence: 99%
“…This was the first report of chickens infected with aMPV/C [11]. Subsequently, aMPV/C was reported to experimentally infect mice and induce strong inflammation in the lungs [12]. Another research study showed that aMPV/C could induce a complete autophagic response, which was partially regulated by ER stress [13].…”
Section: Introductionmentioning
confidence: 95%
“…Recently, aMPV/C and hMPV have been subclassified into the same type based on phylogenetic analysis, while aMPV/A and aMPV/B belong to another type 5 . In addition, aMPV/C has limited cross-reactivity with aMPV/A and aMPV/B in virus neutralization assays 56 . Furthermore, aMPV/C has closer antigenic and genetic relatedness to hMPV than to aMPV/A and aMPV/B 57 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, aMPV/C has closer antigenic and genetic relatedness to hMPV than to aMPV/A and aMPV/B 57 58 . Interestingly, Wei et al demonstrated that the behavior of aMPV/C in mice is similar to that of hMPV, suggesting that aMPV/C might emerge as a zoonotic pathogen 56 . We also showed that the mechanism of trypsin- or low pH-induced membrane fusion mediated through aMPV/C differs from that of aMPV/A and aMPV/B and is more similar to some hMPV strains.…”
Section: Discussionmentioning
confidence: 99%
“…A infecção pelo aMPV causa uma doença respirató-ria aguda caracterizada por descarga nasal e ocular, conjuntivite espumosa, congestão facial, inchaço dos seios infraorbitários, edema submandibular, além de queda de postura e ovos de baixa qualidade em perus (WEI et al, 2014). Em frangos de corte e/ou aves de postura o aMPV está associado a problemas respiratórios, à Síndrome da Cabeça Inchada (SCI), sinais nervosos (torcicolo, opistótono e falta de coordenação) e queda na produção e qualidade dos ovos (ARNS et al, 2000).…”
Section: Introductionunclassified